تكريس التاريخ البشري في شعر الجواهري قراءة نقدية ثقافية - برزنجي, أ.د.إسماعيل إبراهيم مصطفى; محمد, م.م.مهدي حسين (Sulaimani Journal for Humanities, 2023)
The current paper aims to shed light on the extent of the history's influence on the poet and its consecration in his poetry in the form of implicit patterns that carry with them ideas and ideologies that are different from what appears to the reader at first glance. The implicit patterns are not made by the poet, but they infiltrate his poetry and hide among the aesthetics of the verses laden with cultural references that have a negative impact. The paper concluded that the poet's relationship with history is a close one, from which the poet draws his material and ideas, but at the same time the poet carries the burden of the implicit that were embedded in his verses and carried with them the ugly heritage.
Keywords: التاريخ شعر الجواهري الأنساق المضمر النقد الثقافي